2016
DOI: 10.1038/srep20071
|View full text |Cite|
|
Sign up to set email alerts
|

ZnCr2O4 Nanoparticles: Facile Synthesis, Characterization and Photocatalytic Properties

Abstract: In this work, zinc chromite (ZnCr2O4) nanostructures have been synthesized through co-precipitation method. The effect of various parameters such as alkaline agent, pH value, and capping agent type was investigated on purity, particle size and morphology of samples. It was found that particle size and morphology of the products could be greatly influenced via these parameters. The synthesized products were characterized by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…As found in past studies, the lattice parameters computed by the GGA + U method are slightly higher than the experimental ones (by less than 2% Figure S9. It is clear that the DOS at the Fermi energy E F is empty and their band gaps (summarized in Table S7) are within 3 eV, which is in agreement with previous DFT+U studies 29,48 and experiments [49][50][51] . The DFT calculated band gaps of with carbon) and thus the intrinsic conductivity of oxides is not influential.…”
Section: Introductionsupporting
confidence: 90%
“…As found in past studies, the lattice parameters computed by the GGA + U method are slightly higher than the experimental ones (by less than 2% Figure S9. It is clear that the DOS at the Fermi energy E F is empty and their band gaps (summarized in Table S7) are within 3 eV, which is in agreement with previous DFT+U studies 29,48 and experiments [49][50][51] . The DFT calculated band gaps of with carbon) and thus the intrinsic conductivity of oxides is not influential.…”
Section: Introductionsupporting
confidence: 90%
“…A higher temperature of calcination (>1000 • C) is needed for the reactions' completion, which leads to the obtaining of spinel powder with a small surface area [14,15]. Various synthesis methods, such as co-precipitation [16,17], sol-gel [6,18], thermolysis of polymer-metal complex [19], microwave [14,20], and hydrothermal methods [15,21,22] have been investigated in order to obtain spinel powders with higher specific surface areas. Among all these methods, the most efficient one, which considers the lack of stoichiometry control and allows the formation of homogeneous nanoparticles with very good properties for catalytic and photocatalytic usage, is considered to be synthesis at a low temperature, starting from different precursors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Spinel‐type oxides seem to be promising candidates because of their high stability in different media (acidic and basic), containing earth abundant elements and can be easily synthesized in large quantities. In some studies ZnCr 2 O 4 showed very good performances in photo degradation of Reactive Blue 5, Rhodamine B, Methylene blue and Methyl orange, or y‐Eosin, due to a direct bandgap of ca. 3.4 eV and a low absorbance of visible light caused by d–d transitions of Cr 3+ ions.…”
Section: Introductionmentioning
confidence: 99%